2014
DOI: 10.1155/2014/412619
|View full text |Cite
|
Sign up to set email alerts
|

TBT Effects on the Development of Intersex (Ovotestis) in Female Fresh Water PrawnMacrobrachium rosenbergii

Abstract: The impact of tributyltin (TBT) on the female gonad and the endocrine system in Macrobrachium rosenbergii was studied. Prawns were exposed to environmentally realistic concentrations of 10, 100, and 1000 ng/L of TBT for 6 months. Dose dependent effects were noticed in TBT exposed prawns. At 1000 ng/L TBT caused ovotestis formation (formation of male germ cells in ovary). Presence immature oocytes, fusion of developing oocytes, increase in interstitial connective tissues, and its modification into tubular like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…The most frequently reported manifestation of intersex is the presence of single or multiple oocytes which normally grow into the testis (Bahamonde et al, 2013;Nolan et al, 2001;Randak et al, 2009) which is in agreement with previous occurrences reported both in zebrafish (Brion et al, 2004;Hill and Janz, 2003;Örn et al, 2003) and in studies with similar treatments and other fish species (Afonso et al, 2001;Gao et al, 2010;Peranandam et al, 2014). This result indicates that Fad exposure, although potentiating masculinization, may at the concentration used not completely transform females into males, as some of the gonads still present oocytes, or the exposure time was not sufficient to masculinize all females as they have an asynchronous gonad maturation.…”
Section: Discussionsupporting
confidence: 89%
“…The most frequently reported manifestation of intersex is the presence of single or multiple oocytes which normally grow into the testis (Bahamonde et al, 2013;Nolan et al, 2001;Randak et al, 2009) which is in agreement with previous occurrences reported both in zebrafish (Brion et al, 2004;Hill and Janz, 2003;Örn et al, 2003) and in studies with similar treatments and other fish species (Afonso et al, 2001;Gao et al, 2010;Peranandam et al, 2014). This result indicates that Fad exposure, although potentiating masculinization, may at the concentration used not completely transform females into males, as some of the gonads still present oocytes, or the exposure time was not sufficient to masculinize all females as they have an asynchronous gonad maturation.…”
Section: Discussionsupporting
confidence: 89%
“…Imposex is characterized by the formation of male sexual organs such as penis and vas deferens in these females ( 19 , 86 ). Although some studies show an early sexual reversal (intersex) in crustaceans exposed to TBT, these changes are less marked than those occurring in mollusks ( 31 , 88 ). Nevertheless, other detrimental effects on the reproductive system of different species of crustaceans were found in both females and males ( 27 , 88 90 ).…”
Section: Ots Effects On Reproductionmentioning
confidence: 86%
“…Although some studies show an early sexual reversal (intersex) in crustaceans exposed to TBT, these changes are less marked than those occurring in mollusks ( 31 , 88 ). Nevertheless, other detrimental effects on the reproductive system of different species of crustaceans were found in both females and males ( 27 , 88 90 ). The mechanism by which TBT causes these damages is still unclear, and there are different possible sites of action ( 80 , 86 , 89 ).…”
Section: Ots Effects On Reproductionmentioning
confidence: 86%
See 2 more Smart Citations